Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1245/s10434-006-9240-4
|View full text |Cite
|
Sign up to set email alerts
|

Method of Biopsy and Incidence of Positive Margins in Primary Melanoma

Abstract: The presence of tumor at the lateral margin of punch biopsies is an expected result, since this method is often used to diagnose lesions with a large diameter. The presence of positive deep margins in 22% of shave biopsy specimens compromises the ability of this technique to properly stage patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 23 publications
1
48
1
2
Order By: Relevance
“…The various techniques all have advantages and disadvantages. A shave biopsy is generally broader und allows for better evaluation of the epithelium, whereas a punch biopsy provides deeper sections of the corium [58,60,62].…”
Section: Rosementioning
confidence: 99%
“…The various techniques all have advantages and disadvantages. A shave biopsy is generally broader und allows for better evaluation of the epithelium, whereas a punch biopsy provides deeper sections of the corium [58,60,62].…”
Section: Rosementioning
confidence: 99%
“…For a lesion clinically suspicious for cutaneous melanoma, one should ideally perform a narrow excisional biopsy that encompasses the entire breadth of the lesion with clinically negative margins to a depth sufficient to ensure that the lesion is not transected. [8][9][10][11][12][13][14][15][16][17][18] It has been suggested that 1-to 3-mm margins are required to clear the subclinical component of most atypical melanocytic lesions. 1,3,19 This can be accomplished in a number of ways including elliptical or punch excision with sutures, or shave removal to a depth below the anticipated plane of the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Shave biopsy is by far the most common technique employed because of its rapidity and low cost as well as ease of wound care and an optimal cosmetic result. 32,[80][81][82][83] Another utility of the tangential technique is to allow for broad sampling of the lesion in question as opposed to incisional methods. A superficial shave removes mostly epidermis and at times superficial dermis.…”
Section: Methods Of Biopsymentioning
confidence: 99%
“…80,94,[113][114][115][116] Regarding deep margins, concern has arisen over the accuracy of calculating the Breslow depth in shave biopsies. A retrospective analysis of 1784 cases in the 1990's showed that shave biopsy was superior to punch biopsy and curettage in allowing for evaluation of melanoma.…”
Section: Margins and Metastasismentioning
confidence: 99%